Managing the Paralympics - Darcy, Simon, 1964-; Frawley, Stephen, 1969-; Adair, Daryl (Palgrave Macmillan, 2017)
This book critically examines the planning, management, and operations of the world's premier event for Para sport athletes. Noting a lack of research into how these games are planned and managed, the authors of this contributed volume discuss how the Paralympics are essentially different to the Olympics and what this means for their management. Managing the Paralympics explores how the organizers and connected stakeholders effectively organize and deliver the Paralympics, taking into account what has been learned from previous events. Including emergent models of best practice from event management, project management and sport management literature, the book gives an insight into the planning of one of the world's biggest sporting events that encompasses ten impairment types and multiple sport classes within sports.- Resumé vydavatel
Keywords: sportovní management; event management; projektový management; speciální olympiády; paralympionici; sports management; project management; Special Olympics; paralympic sportsmen; elektronické knihy; sborníky; electronic books; papers of several authors